Camrelizumab combined with apatinib in patients with first-line platinum-resistant or PD-1 inhibitor resistant recurrent/metastatic nasopharyngeal carcinoma: a single-arm, phase 2 trial - Yuan, Li; Jia, Guo-Dong; Lv, Xiao-Fei; Xie, Si-Yi; Guo, Shan-Shan; Lin, Da-Feng; Liu, Li-Ting; Luo, Dong-Hua; Li, Yi-Fu; Deng, Shen-Wen; Guo, Ling; Zeng, Mu-Sheng; et al. (Nature communications, 2023)
Immunotherapy combined with antiangiogenic targeted therapy has improved the treatment of certain solid tumors, but effective regimens remain elusive for refractory recurrent/metastatic nasopharyngeal carcinoma (RM-NPC). We conducted a phase 2 trial to evaluate the safety and activity of camrelizumab plus apatinib in platinum-resistant (cohort 1, NCT04547088) and PD-1 inhibitor resistant NPC (cohort 2, NCT04548271). Here we report on the primary outcome of objective response rate (ORR) and secondary endpoints of safety, duration of response, disease control rate, progression-free survival, and overall survival. The primary endpoint of ORR was met for cohort 1 (65%, 95% CI, 49.6–80.4, n = 40) and cohort 2 (34.3%; 95% CI, 17.0–51.8, n = 32). Grade ≥ 3 treatment-related adverse events (TRAE) were reported in 47 (65.3%) of 72 patients. Results of our predefined exploratory investigation of predictive biomarkers show: B cell markers are the most differentially expressed genes in the tumors of responders versus non-responders in cohort 1 and that tertiary lymphoid structure is associated with higher ORR; Angiogenesis gene expression signatures are strongly associated with ORR in cohort 2. Camrelizumab plus apatinib combination effectiveness is associated with high expression of PD-L1, VEGF Receptor 2 and B-cell-related genes signatures. Camrelizumab plus apatinib shows promising efficacy with a measurable safety profile in RM-NPC patients. Combination of immune checkpoint inhibitors with anti-angiogenic targeted therapy has shown efficacy in some solid tumours. Here the authors report the results of a phase 2 trial of camrelizumab (anti-PD1) plus apatinib as a second-line or later-line treatment regimen in platinum-resistant (cohort 1) or PD-1 inhibitor-resistant (cohort 2) Recurrent/Metastatic Nasopharyngeal Carcinoma patients.